Dakwah di Tengah Konsumerisme Kematian: Kajian Simbolik Pemakaman Modern Masyarakat Perkotaan - Al Kahfi (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This article examines the phenomenon of consumerism in the realm of death through the presence of modern cemeteries, which have emerged as new symbols of status and lifestyle in urban areas due to urbanization, land scarcity, and unequal access to burial spaces. This study aims to analyze how modern cemeteries reflect the symbolic construction of death and how this phenomenon interacts with the values of Islamic da’wah. Using a descriptive qualitative approach and a symbolic-cultural case study, this article explores narratives of spirituality, aesthetics, and symbolic capital. The analysis applies Jean Baudrillard’s theory of symbolic consumption and is linked to the perspective of Islamic da’wah. This study finds that modern cemeteries are not merely a solution to land scarcity, but also symbols of status shaped by spiritual and aesthetic narratives. This phenomenon reflects a paradox between Islamic values of simplicity and materialistic death practices, yet it also opens space for contextual da’wah. Islamic da’wah needs to adopt a more contextual and humanistic approach—not to reject the existence of modern cemeteries, but to offer spiritual guidance and educational values within them. In this way, Islamic teachings on simplicity, equality, and reflection on death can remain integrated within the realities of modern urban life.